The ‘Comparative Logic’ and Why We Need to Explain Interlanguage Grammars - Domínguez, Laura; Arche, María J. (Frontiers in Psychology, 2021)
In this paper we argue that the Comparative Fallacy (Bley Vroman 1983), which warns against comparisons between native speakers and learners in Second Language Acquisition research, is not justified on either theoretical or methodological grounds and should be abandoned, as it contravenes the explanatory nature of SLA research. We argue that for SLA to be able to provide meaningful explanations, grammatical comparisons with a baseline (usually of native speakers although not always the case) are not only justified but necessary, a position which we call the ‘Comparative Logic’. The methodological choices assumed by this position ensure that interlanguage grammars are analysed on their own right and respecting their own principles. Related issues such as why we focus on the native speaker and why investigating deficits in linguistic-cognitive SLA is essential in our field are discussed as well.